Production of S-(+)-ibuprofen from a nitrile compound by Acinetobacter sp. strain AK226. - Yamamoto, K (1990)
S-(+)-2-(4'-Isobutylphenyl)propionic acid [S-(+)-ibuprofen] was produced from racemic 2-(4'-isobutylphenyl)propionitrile (Ibu-CN) by an isolated bacterial strain, Acinetobacter sp. strain AK226. Ammonium acetate, acetonitrile, or n-butyronitrile as a carbon source in the culture medium was effective for bacterial growth and induction of this activity. The optimum pH of the reaction was around 8.0. S-(+)-Ibuprofen formed from Ibu-CN by resting cells was present in a 95% enantiomeric excess. Acinetobacter sp. strain AK226 appeared to possess a nitrilase for Ibu-CN because 2-(4'-isobutylphenyl)propionamide was not detected in the reaction mixture and 2-(4'-isobutylphenyl)propionamide was not hydrolyzed to S-(+)-ibuprofen. Since S-(+)-ibuprofen was preferentially produced while the R enantiomer of Ibu-CN was left almost intact over the time course of the reaction, the putative nitrilase appeared to be highly specific for the S enantiomer of Ibu-CN.